Treatment method for efficient photocatalytic degradation of methylene blue in water
By preparing a combination of porous photocatalysts with PMS, pH regulator and pH stabilizer, photocatalysis is performed using xenon lamp sources, which solves the problems of low degradation efficiency of azo dyes and high cost of transition metal activation in textile industry wastewater, and realizes the Efficient and economical methylene blue removal effect.
Patent Information
- Application Number
- CN202411524091.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art has low degradation efficiency when treating printing and dyeing wastewater generated in the textile industry, especially azo dyes, and the use of transition metals to activate peroxy monosulfates has high cost and potential secondary pollution problems.
The preparation of porous photocatalyst is synthesized using ore solid waste, combined with peroxy monosulfate (PMS), pH adjuster and pH stabilizer, and photocatalytic degradation is carried out through xenon lamp light source, achieving efficient removal of methylene blue.
It improves the removal effect of organic matter in water, reduces the cost of organic matter treatment, realizes the secondary utilization of waste resources, and maintains the pH value during photocatalysis, with a removal rate of more than 80%.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a method for efficiently photocatalytically degrading methylene blue in water. Background Art
[0002] In the textile industry, organic wastewater generated in the printing and dyeing process has become the main environmental burden in the industry. With the expansion of China's textile industry production capacity and the increase in international market share, the wastewater discharge dilemma faced by the industry has become increasingly prominent. Data show that in 2019, China's textile products accounted for 39.2% of the global export market. The huge production capacity corresponds to an astonishing consumption of water resources. On average, 100 to 200 tons of clean water may be required to produce one ton of textile products, and its annual wastewater discharge can reach 2 billion tons. This makes the textile industry a major discharger of industrial wastewater, especially printing and dyeing wastewater discharge, which is the dominant part, accounting for up to 70% to 80%.
[0003] Printing and dyeing wastewater has multiple significant characteristics: first, its chromaticity is high, usually between 50 and 2500 degrees, reflecting the high concentration of dyes in the wastewater; second, its chemical oxygen demand (COD) is high, ranging from 150 to 30,000 mg / L, revealing the abundance of organic pollutants in the wastewater; in addition, this type of wastewater is also characterized by strong toxicity, high salt levels, and excessive suspended solids concentration. The high chromaticity in the wastewater is due to the chromogenic structural units and auxiliary color units inside the dye entering the wastewater, especially azo dyes, which are known for their stable chemical structure and poor biodegradability, accounting for about 60%-70% of the dyes, greatly increasing the difficulty of printing and dyeing wastewater treatment. Currently, various technical means are used for the treatment of printing and dyeing wastewater, including chemical oxidation, physical and chemical methods, electrochemical decomposition, photocatalytic oxidation, and biological treatment.
[0004] Photocatalysis is considered as the best pollutant treatment method due to its high efficiency, cost-effectiveness and low environmental impact. Advanced oxidation processes are a class of technologies that use catalysts and electro-optical radiation to generate hydroxyl radicals and sulfate ions through the activation of persulfate or peroxymonosulfate (PMS). These processes involve addition, substitution, electron transfer and other interaction reactions between free radicals and organic matter. Peroxymonosulfate has attracted much attention due to its stability, solubility and strong redox ability, and can effectively degrade various organic pollutants such as azo dyes and phenolic compounds.
[0005] Studies have shown that transition metals such as cobalt, iron and copper have a promoting effect on the activation of PMS and improve the catalytic activity of PMS. However, there are some disadvantages of using transition metals to activate PMS, including rising costs and potential secondary pollution problems. Summary of the invention
[0006] The purpose of the present invention is to solve the defects of the prior art and provide a treatment method for efficiently photocatalytically degrading methylene blue in water. The method comprises the following steps: preparing a photocatalyst for degrading methylene blue in water, then adding the photocatalyst, PMS, a pH regulator and a pH stabilizer into contaminated water containing methylene blue, first stirring the water to reach an adsorption-desorption equilibrium, and then irradiating the water with a xenon lamp light source to remove the methylene blue pollutant in the water. The photocatalyst prepared by the present invention is synthesized from ore solid waste, has a rich pore structure, and can provide more photocatalytic active sites; while being able to improve the removal effect of organic matter in water, it can reduce the cost of organic matter treatment and realize the secondary utilization of waste resources; the pH stabilizer of the present invention can be used to keep the pH value in the photocatalytic process stable, thereby better removing the methylene blue pollutant. The removal rate of methylene blue in water by the present invention is high, and the present invention has good application prospects.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for efficiently photocatalytically degrading methylene blue in water comprises the following steps:
[0009] Step S1: Preparation of porous photocatalyst
[0010] Step S11: mixing the iron tailings and steel slag in proportion to obtain solid powder A;
[0011] Step S12: mixing water glass and carbide slag in proportion, stirring and mixing, and then standing for a period of time to obtain an alkali activator;
[0012] Step S13: stirring the hydrogen peroxide solution and letting it stand for a period of time to obtain a foaming agent;
[0013] Step S14: adding the solid powder A obtained in step S11 to the alkali activator obtained in step S12; after mixing, mechanically stirring to obtain a mixed slurry B;
[0014] Step S15: adding the foaming agent obtained in step S13 to the mixed slurry B obtained in step S14, and then mechanically stirring to obtain a mixed slurry C;
[0015] Step S16: pouring the mixed slurry C into the mold and continuously vibrating to expel air from the slurry;
[0016] Step S17: Seal the sample together with the mold, cure it at room temperature and in an oven to form it, cure it at room temperature after demoulding, and obtain a porous photocatalyst after crushing.
[0017] Step S2: Degradation of methylene blue
[0018] The porous photocatalyst obtained in step S1 is mixed with wastewater containing methylene blue, and potassium peroxymonosulfate PMS is added, and then a pH regulator and a pH stabilizer are added to adjust the pH to a target value, and stirred in the dark to achieve adsorption-desorption equilibrium; and stirred at the same time under the illumination of a xenon lamp light source, so as to remove the methylene blue pollutant in the water;
[0019] The mass fraction of iron tailings in the solid powder A is 70%; the mass fraction of steel slag is 30%; the mass ratio of water glass to carbide slag is 1-4:4-1; the mass ratio of water glass to solid powder A is 1-4:10; the mass ratio of carbide slag to solid powder A is 1-4:10; the mass ratio of hydrogen peroxide solution to solid powder is 0.2-2.0:100; the mass ratio of foam stabilizer to solid powder is 0.8-1.0:100; the foam stabilizer is sodium dodecyl sulfate SDS;
[0020] The pH adjuster is sodium hydroxide or hydrochloric acid; the pH stabilizer is one or more of sodium acetate and sodium sulfide.
[0021] Furthermore, the mass percentage of each component in the iron tailings is: SiO 2 30%-50%, Al 2 O 3 10%-20%, Fe 2 O 3 20%-30%, CaO 5%-10%, MgO 1%-3%, K 2 O 1%-3%, Na 2 O 1%-3%, TiO 2 1%-2%, MnO0.1%-0.5%, and its loss on ignition is 0.4%-1%.
[0022] Furthermore, the particle size of the iron tailings is less than 0.070 mm and needs to be calcined at 300° C.-700° C. for 1-3 hours before use; the particle size of the steel slag is less than 0.070 mm.
[0023] Furthermore, the modulus of the water glass is 3.3, and the solid content is 34 wt %; the concentration of the hydrogen peroxide solution is 10 wt %-30 wt %.
[0024] Furthermore, the room temperature curing temperature is 24-28°C, the curing time is 12-48 hours, the oven curing temperature is 80-150°C, the curing time is 8-12 hours, and then the room temperature curing time is 7-14 days.
[0025] Furthermore, the light-proof stirring time is 30-60 minutes.
[0026] Furthermore, the concentration of methylene blue in the wastewater is 5-20 mg / L, and the peak value of the ultraviolet spectrum is 664 nm.
[0027] Furthermore, the addition amount of potassium permonosulfate PMS is 10-25 mg / L, the intensity of the xenon lamp light source is 70-80 cd, the illumination time is 30-60 min, and the stirring rate is 800-1000 r / min.
[0028] Furthermore, the pH is adjusted to 7-12, and the mass ratio of the porous photocatalyst to the wastewater is 1-1.5:1000.
[0029] Furthermore, the concentration of the pH stabilizer in the wastewater is 3-10 mmol / L.
[0030] The beneficial effects of the present invention are:
[0031] The invention discloses a method for efficiently photocatalytically degrading methylene blue in water. The method comprises the following steps: preparing a photocatalyst for degrading methylene blue in water, then adding the photocatalyst, PMS, a pH regulator and a pH stabilizer into contaminated water containing methylene blue, first stirring the water to achieve adsorption-desorption equilibrium, and then irradiating the water with a xenon lamp light source to remove the methylene blue pollutant in the water. The photocatalyst prepared by the invention is synthesized from ore solid waste, has a rich pore structure, and can provide more photocatalytic active sites; while improving the removal effect of organic matter in water, it can reduce the cost of organic matter treatment and realize the secondary utilization of waste resources; the pH stabilizer of the invention can keep the pH value in the photocatalytic process stable, thereby better removing the methylene blue pollutant; the removal rate of the methylene blue in water by the invention reaches more than 80%, and the invention has good application prospects. DETAILED DESCRIPTION
[0032] The following will further describe the optimized implementation of the present invention. Although the following describes the optimized implementation of the present invention, it should be understood that the present invention can be implemented in various forms and should not be limited by the implementation described here. On the contrary, these implementations are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art. At the same time, the protection scope of the present invention includes but is not limited to the following:
[0033] In the following examples, the mass percentage of the geopolymer porous material components is: iron tailings: steel slag is 70%:30%. Water glass is a commercially available chemical agent; the modulus is 3.3, the solid content is 34wt%, the Baume degree is 40, the amount of water glass added is 10wt%-40wt% of the solid powder, and the amount of calcium carbide slag added is 40wt%-10wt% of the solid powder. The purity of the hydrogen peroxide used is analytically pure, the percentage content is 30%, and the amount of addition is 0.2wt%-2.0wt% of the solid powder. The amount of SDS added is 0.8wt%-1.0wt% of the solid powder. The curing time is 24h at room temperature, 8h in an oven at 150°C, and then 7d at room temperature.
[0034] The water used in the following examples is tap water.
[0035] The concentration of methylene blue in the embodiment of the present invention is determined by the absorption peak intensity of an ultraviolet spectrophotometer at 664 nm.
[0036] Example 1
[0037] The porous photocatalyst of this embodiment includes iron tailings, steel slag, an alkali activator, a foaming agent and a foam stabilizer. The mass fraction of the iron tailings in the solid powder is 70% (70g), and the mass fraction of the steel slag is 30% (30g); the modulus of water glass in the alkali activator is 3.3, and the addition amount is 25wt% (25g) of the solid powder, and the addition amount of calcium carbide slag is 25wt% (25g) of the solid powder; the addition amount of hydrogen peroxide solution in the foaming agent is 1.1wt% (1.1g) of the solid powder; the addition amount of SDS is 0.8wt% (0.8g) of the solid powder.
[0038] After the iron tailings and steel slag are mixed evenly in the above proportion, water glass and carbide slag are added in proportion, and after mechanical stirring, a foaming agent and SDS are added. Then, the mixture is poured into a mold, cured at room temperature of 25°C for 24 hours, then cured in an oven at 150°C for 8 hours, and then cured at room temperature for 7 days. The porous photocatalyst is obtained after crushing.
[0039] Take 100ml, 20ppm, 35℃ methylene blue solution as the target pollutant, weigh 150mg porous photocatalyst and 15mg PMS and add them to the solution, then add pH adjuster sodium hydroxide and pH stabilizer sodium acetate (10mmol / L), adjust pH to the target value of 9, stir for 30min in dark to achieve adsorption-desorption equilibrium. Turn on the xenon light source, irradiate for 30min at a distance of about 15cm from the beaker mouth, take samples every 5min, and use UV spectrophotometer for detection.
[0040] Example 2
[0041] The porous photocatalyst of this embodiment includes iron tailings, steel slag, alkali activator, water reducer, foaming agent and foam stabilizer. The mass fraction of iron tailings in the solid powder is 70% (70g), and the mass fraction of steel slag is 30% (30g); the modulus of water glass in the alkali activator is 3.3, and the addition amount is 10wt% (10g) of the solid powder, and the addition amount of calcium carbide slag is 40wt% (40g) of the solid powder; the addition amount of hydrogen peroxide solution in the foaming agent is 1.1wt% (1.1g) of the solid powder; the addition amount of the foam stabilizer is 0.8wt% of the solid powder.
[0042] After mixing the iron tailings and steel slag in the above proportions, add water glass and carbide slag in proportion, stir mechanically and add foaming agent and SDS, then pour into a mold, cure at room temperature 25°C for 24 hours, then cure in an oven at 150°C for 8 hours, and then cure at room temperature for 7 days.
[0043] Take 100ml, 10ppm, 30℃ methylene blue solution as the target pollutant, weigh 100mg porous photocatalyst and 10mg PMS and add them to the solution, then add pH adjuster sodium hydroxide and pH stabilizer sodium acetate (3mmol / L), adjust pH to the target value of 7, stir for 30min in dark to reach adsorption-desorption equilibrium. Turn on the xenon light source, irradiate for 30min at a distance of about 15cm from the beaker mouth, take samples every 5min, and use UV spectrophotometer for detection.
[0044] Example 3
[0045] The porous photocatalyst of this embodiment includes iron tailings, steel slag, alkali activator, water reducer, foaming agent and foam stabilizer. The mass fraction of iron tailings in the solid powder is 70% (70g), and the mass fraction of steel slag is 30% (30g); the modulus of water glass in the alkali activator is 3.3, and the addition amount is 40wt% (40g) of the solid powder, and the addition amount of calcium carbide slag is 10wt% (10g) of the solid powder; the addition amount of hydrogen peroxide solution in the foaming agent is 1.1wt% (1.1g) of the solid powder; the addition amount of the foam stabilizer is 1.0wt% (1.0g) of the solid powder.
[0046] After mixing the iron tailings and steel slag in the above proportions, add water glass and carbide slag in proportion, stir mechanically and add foaming agent and SDS, then pour into a mold, cure at room temperature 25°C for 24 hours, then cure in an oven at 150°C for 8 hours, and then cure at room temperature for 7 days.
[0047] Take 100ml, 5mg / L, 25℃ methylene blue solution as the target pollutant, weigh 100mg porous photocatalyst and 25mg PMS and add them to the solution, then add pH adjuster sodium hydroxide and pH stabilizer sodium acetate (5mmol / L), adjust the pH to the target value of 12, stir for 30min in dark to achieve adsorption-desorption equilibrium. Turn on the xenon light source, irradiate for 30min at a distance of about 15cm from the beaker mouth, take samples every 5min, and use UV spectrophotometer for detection.
[0048] The degradation effect of methylene blue in Examples 1-3 was tested, and the results are shown in Table 1.
[0049] Table 1 Degradation effect of methylene blue in Example
[0050] Example Iron tailings: steel slag wt% Water glass: carbide slag wt% MB removal % 1 70:30 25:25 89.25 2 70:30 10:40 84.38 3 70:30 40:10 96.68
[0051] It can be seen from Table 1 that the porous photocatalyst has a good degradation effect on methylene blue, which is mainly due to the excellent pore structure of the porous photocatalyst and the rich iron element in the steel slag, which generates a large number of active free radicals such as SO 4 ·- , ·O 2 - and ·OH, these active free radicals can participate in oxidation reactions, and they deprive electrons from MB molecules. Sulfate radicals and hydroxyl radicals are both highly oxidizing substances. In these reactions, MB molecules lose electrons to form oxidation products. This process may cause molecular breakage or the formation of products with higher oxidation states. The free radicals react with carbon-carbon or carbon-hydrogen bonds in MB molecules, resulting in chain breakage or the formation of new chemical bonds. After adding the pH stabilizer of the present application, the reaction system can be maintained at a higher pH. At a higher pH, PMS can be better activated, and SO4·- will undergo a substantial conversion to ·OH, thereby showing a better removal rate; it is beneficial to the degradation of MB and has an excellent degradation effect and efficiency.
[0052] In summary, the present invention discloses a method for efficiently photocatalytically degrading methylene blue in water. The method comprises the steps of preparing a photocatalyst for degrading methylene blue in water, then adding the photocatalyst, PMS, a pH regulator and a pH stabilizer into contaminated water containing methylene blue, first stirring the water to achieve adsorption-desorption equilibrium, and then irradiating the water with a xenon lamp light source to remove the methylene blue pollutant in the water. The photocatalyst prepared by the present invention is synthesized from ore solid waste, has a rich pore structure, and can provide more photocatalytic active sites; while being able to improve the removal effect of organic matter in water, it can reduce the cost of organic matter treatment and realize the secondary utilization of waste resources; the pH stabilizer of the present invention can keep the pH value in the photocatalytic process stable, thereby better removing the methylene blue pollutant. The removal rate of methylene blue in water by the present invention reaches more than 80%, and the present invention has good application prospects.
[0053] Thus far, various embodiments of the present invention have been described, and the above description is exemplary, not exhaustive, and is not limited to the described embodiments. Without departing from the scope and spirit of the described embodiments, many modifications and variations are within the scope of the present invention for those of ordinary skill in the art.
Claims
1. A method for efficiently photocatalytically degrading methylene blue in water, characterized in that: The processing method comprises the following steps: Step S1: Preparation of porous photocatalyst Step S11: mixing the iron tailings and steel slag in proportion to obtain solid powder A; Step S12: mixing water glass and carbide slag in proportion, stirring and mixing, and then standing for a period of time to obtain an alkali activator; Step S13: stirring the hydrogen peroxide solution and letting it stand for a period of time to obtain a foaming agent; Step S14: adding the solid powder A obtained in step S11 to the alkali activator obtained in step S12; after mixing, mechanically stirring to obtain a mixed slurry B; Step S15: adding the foaming agent obtained in step S13 to the mixed slurry B obtained in step S14, and then mechanically stirring to obtain a mixed slurry C; Step S16: pouring the mixed slurry C into the mold and continuously vibrating to expel air from the slurry; Step S17: Seal the sample together with the mold, cure it at room temperature and in an oven to form it, cure it at room temperature after demoulding, and obtain a porous photocatalyst after crushing. Step S2: Degradation of methylene blue The porous photocatalyst obtained in step S1 is mixed with wastewater containing methylene blue, and potassium peroxymonosulfate PMS is added, and then a pH regulator and a pH stabilizer are added to adjust the pH to a target value, and stirred in the dark to achieve adsorption-desorption equilibrium; and stirred at the same time under the illumination of a xenon lamp light source, so as to remove the methylene blue pollutant in the water; The mass fraction of iron tailings in the solid powder A is 70%; the mass fraction of steel slag is 30%; the mass ratio of water glass to carbide slag is 1-4:4-1; the mass ratio of water glass to solid powder A is 1-4:10; the mass ratio of carbide slag to solid powder A is 1-4:10; the mass ratio of hydrogen peroxide solution to solid powder is 0.2-2.0:100; the mass ratio of foam stabilizer to solid powder is 0.8-1.0:100; the foam stabilizer is sodium dodecyl sulfate SDS; The pH adjuster is sodium hydroxide or hydrochloric acid; the pH stabilizer is one or more of sodium acetate and sodium sulfide.
2. A method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The mass percentage of each component in the iron tailings is: SiO2 30%-50%, Al2O3 10%-20%, Fe2O3 20%-30%, CaO 5%-10%, MgO 1%-3%, K2O 1%-3%, Na2O 1%-3%, TiO2 1%-2%, MnO 0.1%-0.5%, and the ignition loss is 0.4%-1%.
3. A method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The particle size of the iron tailings is less than 0.070 mm and needs to be calcined at 300° C.-700° C. for 1-3 hours before use; the particle size of the steel slag is less than 0.070 mm.
4. A method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The modulus of the water glass is 3.3, and the solid content is 34 wt %; the concentration of the hydrogen peroxide solution is 10 wt %-30 wt %.
5. A method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The room temperature curing temperature is 24-28°C, the curing time is 12-48 hours, the oven curing temperature is 80-150°C, the curing time is 8-12 hours, and then the room temperature curing time is 7-14 days.
6. A method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The light-proof stirring time is 30-60 min.
7. A method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The concentration of methylene blue in the wastewater is 5-20 mg / L, and the peak value of the ultraviolet spectrum is 664 nm.
8. The method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The addition amount of the potassium permonosulfate PMS is 10-25 mg / L, the intensity of the xenon lamp light source is 70-80 cd, the illumination time is 30-60 min, and the stirring rate is 800-1000 r / min.
9. A method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The pH is adjusted to 7-12, and the mass ratio of the porous photocatalyst to the wastewater is 1-1.5:1000.
10. The method for efficiently photocatalytically degrading methylene blue in water according to claim 1, characterized in that: The concentration of the pH stabilizer in the wastewater is 3-10 mmol / L.